Ethnozootechnical characterization and analysis of the genetic situation of the Chato Murciano pig breed - Poto A.; Martínez M.; Peinado B.; Barba C.; Lobera J.B.; Delgado J.V. (Tradition and innovation in Mediterranean pig production, 2000)
At present, 40 adult animals share the total population of the Chato Murciano pig breed. This is one of the most endangered native pig breeds of Spain. This paper, develops the morphological characterization of this breed studying thirteen quantitative variables and six qualitative variables from a sample of 24 male and female adult animals. It has also been carried out the evaluation of individuals and the population inbreeding levels of the breed.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)